Data intensive scientific analysis with grid computing - Terzo, Olivier; Mossucca, Lorenzo; Cucca, Manuela; Notarpietro, Riccardo (Zielona Góra: Uniwersytet Zielonogórski)
At the end of September 2009, a new Italian GPS receiver for radio occultation was launched from the Satish Dhawan Space Center (Sriharikota, India) on the Indian Remote Sensing OCEANSAT-2 satellite. The Italian Space Agency has established a set of Italian universities and research centers to implement the overall processing radio occultation chain. After a brief description of the adopted algorithms, which can be used to characterize the temperature, pressure and humidity, the contribution will focus on a method for automatic processing these data, based on the use of a distributed architecture. This paper aims at being a possible application of grid computing for scientific research.
Keywords: grid computing; GPS radio occultation; scheduler; agent; e-science